2017
DOI: 10.1186/s12936-017-2115-2
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance in Anopheles arabiensis from Ethiopia (2012–2016): a nationwide study for insecticide resistance monitoring

Abstract: BackgroundIndoor residual spraying (IRS) and long-lasting insecticidal nets (LLINs) remain the cornerstones of malaria vector control. However, the development of insecticide resistance and its implications for operational failure of preventative strategies are of concern. The aim of this study was to characterize insecticide resistance among Anopheles arabiensis populations in Ethiopia and describe temporal and spatial patterns of resistance between 2012 and 2016.MethodsBetween 2012 and 2016, resistance statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
61
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 37 publications
7
61
1
Order By: Relevance
“…arabiensis against pyrethroids and DDT is widespread. 10 In many Ethiopian An. arabiensis populations an association between the kdr mutation in the VGSC and resistance to pyrethroids and DDT resistance has been observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…arabiensis against pyrethroids and DDT is widespread. 10 In many Ethiopian An. arabiensis populations an association between the kdr mutation in the VGSC and resistance to pyrethroids and DDT resistance has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…arabiensis populations an association between the kdr mutation in the VGSC and resistance to pyrethroids and DDT resistance has been observed. 7, 9, 10, 12 However, a number of studies have also pointed to increased detoxification as important in resistant populations, as the resistance phenotype is strong, and because kdr mutations were not fixed at the population level. 10, 12 Metabolic resistance has been observed in other pyrethroid and DDT resistant An.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High levels of insecticide resistance have also been reported for An. arabiensis in many countries, including Ethiopia, where we recently surveyed several populations across the country and showed that these An. arabiensis populations exhibited countrywide resistance against DDT and the pyrethroid deltamethrin …”
Section: Introductionmentioning
confidence: 99%